Measuring information processing speed in Multiple Sclerosis – PASAT and SDMT what are the differences? - Neves, M.; Sousa, C.; Passos, A. M.; Ferreira, A.; Sá, M.J. (3rd International Porto Congress of Multiple Sclerosis, 2015)
The reduction in information processing speed (IPS) seems to be a key deficit in Multiple Sclerosis (MS) [1]. The Paced Auditory Serial Addition Test (PASAT) and the Symbol Digit Modalities Test (SDMT) are generally used to assess this domain as they both seem to be sensitive to the slow IPS and to early cognitive deficits [2]. However, recently some concerns regarding the use of the PASAT have been expressed because it is not well tolerated by patients and healthy participants (it is associated with high levels of anxiety), and it is prone to practice effects. This can result in misleading conclusions about participant’s cognitive performance. SDMT is user-friendly, easy and a quicker test, whose execution is not affected by mathematical capabilities [3]. Some studies have showed that the execution of SDMT seems to be more frequently impaired in MS patients than the execution of PASAT, suggesting higher sensitivity toward the cognitive impairments of this clinical population [3]. Fatigue is one of the most commonly debilitating symptoms of MS and has two main components: physical and cognitive. No association has been found between reports of subjective fatigue and cognitive impairment. However, decrements in performance over time in tasks that require sustained mental effort have suggested that fatigue might affect performance [3,4].